The Efficacy and Safety of the Chinese Herbal Formula, JTTZ, for the Treatment of Type 2 Diabetes with Obesity and Hyperlipidemia: A Multicenter Randomized, Positive-Controlled, Open-Label Clinical Trial - Xiaotong Yu; Lipeng Xu; Qiang Zhou; Shengping Wu; Jiaxing Tian; Chunli Piao; Hailong Guo; Jun Zhang; Liping Li; Shentao Wu; Meizhen Guo; Yuzhi Hong; et al. (International Journal of Endocrinology)
Background and Aim. Studies have shown an increasing number of type 2 diabetes (T2D) patients with concomitant obesity and hyperlipidemia syndromes, resulting from relevant metabolic disorders. However, there are few medications and therapies, which can thoroughly address these issues. Therefore, the current study evaluated the efficacy and safety of using JTTZ, a Chinese herbal formula, to treat T2D with obesity and hyperlipidemia. Methods. A total of 450 participants with T2D (HbA1c ≥ 7.0%; waist circumference ≥ 90 cm and 80 cm in males and females, resp.; and triglycerides (TG) ≥ 1.7 mmol/L) were randomly assigned, in equal proportions, to two groups in this multicenter randomized, positive-controlled, open-label trial. One group received JTTZ formula, and the other received metformin (MET) for 12 consecutive weeks. The primary efficacy outcomes were changes in HbA1c, TG, weight, and waist circumference. Adverse reactions and hypoglycemia were monitored. Results. HbA1c decreased by 0.75 ± 1.32% and 0.71 ± 1.2% in the JTTZ and MET groups, respectively, after 12 weeks of treatment. TG levels in the JTTZ and MET groups were reduced by 0.64 ± 2.37 mmol/L and 0.37 ± 2.18 mmol/L, respectively. Weight was decreased by 2.47 ± 2.71 kg in the JTTZ group and by 2.03 ± 2.36 kg in the MET group. JTTZ also appeared to alleviate insulin resistance and increase HOMA-β. In addition, symptoms were significantly relieved in participants in the JTTZ group compared to those in the MET group. One case of hypoglycemia was reported in the MET group. No severe adverse events were reported in either group. Conclusions. The JTTZ formula led to safe and significant improvements in the blood glucose, blood lipids, and weight levels; relieved symptoms; and enhanced β cell function for T2D patients with obesity and hyperlipidemia. The JTTZ formula has shown that it could potentially be developed as an alternative medicine for patients with T2D, particularly those who cannot tolerate metformin or other hypoglycemic drugs. This trial was registered with Clinicaltrials.gov NCT01471275.